2017
DOI: 10.3892/ol.2017.6001
|View full text |Cite
|
Sign up to set email alerts
|

B-cell specific Moloney leukemia virus insert site 1 and peptidyl arginine deiminase IV positively regulate carcinogenesis and progression of esophageal squamous cell carcinoma

Abstract: Abstract. High expression of B-cell specific Moloney leukemia virus insert site 1 (Bmi-1) and peptidyl arginine deiminase IV (PADI4) is associated with esophageal carcinoma. However, few studies have investigated the association between the Bmi-1 and PADI4 genes. The aim of the present study was to evaluate the expression of Bmi-1 and PADI4 and identify the association between the Bmi-1 and PADI4 genes in esophageal squamous cell carcinoma (ESCC) tissues. Bmi-1 and PADI4 gene expression levels were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It has been found that tumors, including squamous cell esophageal carcinoma, have an abnormally increased expression in PADI4. Furthermore, this increase has been associated with carcinogenesis, progress, and metastasis in other tumors [44]. However, expression decreases when the tumor is extirpated [45].…”
Section: Citrullination Pad and Physiopathologymentioning
confidence: 99%
“…It has been found that tumors, including squamous cell esophageal carcinoma, have an abnormally increased expression in PADI4. Furthermore, this increase has been associated with carcinogenesis, progress, and metastasis in other tumors [44]. However, expression decreases when the tumor is extirpated [45].…”
Section: Citrullination Pad and Physiopathologymentioning
confidence: 99%
“…In esophageal squamous cell carcinoma (ESCC), PADI4 can stimulate the growth of ESCC cells and upregulate CA9 to promote ESCC metastasis ( 171 ). PADI4 synergizes with B-cell-specific Moloney leukemia virus insertion site 1 (Bmi-1) to promote the carcinogenesis and progression of ESCC ( 172 ). In prolactinomas and growing prolactinomas, PADI2 and PADI4 can promote the proliferation of cancer cells by catalyzing the citrullination of histones and upregulating the oncogenes HMGA1, N-MYC and IGF-1 ( 149 ).…”
Section: The Padi Family and Cancermentioning
confidence: 99%